A general doping rule: rational design of Ir-doped catalysts for the oxygen evolution reaction. Issue 96 (23rd November 2020) - Zhou, Chuan; Yuan, Haiyang; Hu, P.; Wang, Haifeng
Abstract : Revealing how to rationally select a suitable dopant or the host counterpart is greatly important for optimizing the catalytic activity of transition metal oxides (TMOs). Abstract : Revealing how to rationally select a suitable dopant or the host counterpart is greatly important for optimizing the catalytic activity of transition metal oxides (TMOs). We systematically report the adsorption trends of atomic O and H, two selected representative adsorbates, on numerous doped rutile-type TMO surfaces under two different doping modes, aiming to demonstrate adsorption energy (AE) variations of different adsorbates across doped TMO surfaces. A "host–guest interaction" induced adsorption tuning rule for the ternary doping systems is identified, which rationally directs the proposal of cost-effective Ir-doped CrO2 or MnO2 catalysts for the electrocatalytic oxygen evolution reaction compared with the common IrO2 .